Case Study: Money Management in Kosovo Sports - Enver Tahiraj; Iber Alaj (Universitas Majalengka, 2023)
Sport in the country is supported through program policies and is also supported in its development even with the difficulties that our society and the sports activity of the country has gone through. The management of sports clubs, federations and sports organizations in general develop their activities facing difficulties of a material nature when it comes to participation in international competitions. Therefore, this paper presents the management of money in sports organizations, infrastructure and other stakeholders. This paper is presented as a model, which has to do with the management, sports, infrastructural capacities that are at the moment, then also the distribution of the budget for federations, clubs, sports infrastructure and other organizations that perform these activities. The management of money for sports in the country has been executed for about 35 sports federations with about 867 sports clubs, where in total approximately 81.041 participate in sports activities, of which 67.583 are men and 13,458 women, and their amount spent was about 14,247,919 euro from the revenues of 18.489.005 euro that were from the country’s government. The management of money for sports in the country would open the way if appropriate measures are taken to increase the budget by engaging serious investors in terms of sports infrastructure in public- private partnerships, where this would then affect the addition of sports facilities and their management as rationally as possible where sports activities would then be increased and then this would also bring incomes. Meanwhile, sports organizations should be further supported in the operationalization of fiscal facilities for companies that are helping clubs and federations that wish to enter sports sponsorship, where this would also be pushing force in the development and improvement of sports and its conditions for the progress of sports activities.